2018
DOI: 10.22146/jh.36682
|View full text |Cite
|
Sign up to set email alerts
|

Family Intervention in The Problem of Maternal Death: A Case Study of Pregnant Women in Mbojo, Bima, West Nusa Tenggara

Abstract: In 2015, the maternal mortality rate in Bima was recorded as 3 cases per 1,000 births, equivalent to 300 maternal deaths per 100,000 births. Although this number is low, it is much higher than the zero mortality rate set by the Sustainable Development Goals. This study discusses the family and community aspects of the maternal health framework, reading the gendered symbolic violence that affect maternal health in Jatibaru Village, Asakota, Bima, West Nusa Tenggara. Data was collected using an ethnographic appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
1
0
0
Order By: Relevance
“…This study found that the husband, mother in-law, the mother and grandmother to the pregnant woman and the wider community are very influential in deciding the woman"s delivery location. These findings are similar to those of Triratnawati and Izdiha (2018). In their study titled Family Intervention in the problem of Maternal Death: A case study of pregnant women in Mbojo, Bima, West Nusa TenggaraTriratnawati and Izdiha (2018) found that the husband, biological mother, mother in-law significantly influenced how the pregnant woman access health care services(p270) including where the woman should give birth.…”
Section: Discussionsupporting
confidence: 62%
“…This study found that the husband, mother in-law, the mother and grandmother to the pregnant woman and the wider community are very influential in deciding the woman"s delivery location. These findings are similar to those of Triratnawati and Izdiha (2018). In their study titled Family Intervention in the problem of Maternal Death: A case study of pregnant women in Mbojo, Bima, West Nusa TenggaraTriratnawati and Izdiha (2018) found that the husband, biological mother, mother in-law significantly influenced how the pregnant woman access health care services(p270) including where the woman should give birth.…”
Section: Discussionsupporting
confidence: 62%